Pengaruh Sistem Informasi Akuntansi, Pengawasan Internal Dan Key Performance Indicators (KPI) Terhadap Kinerja Pegawai Dengan Motivasi Bekerja Sebagai Variabel Moderating Di Perum Perumnas Regional I Medan - Rozi, Fachrur; Sari, Maya; Astuti, Widia (Jurnal Riset Akuntansi dan Bisnis, 2021)
The purpose of this study was to analyze the effect of Accounting Information Systems, Internal Controls and Key Performance Indicators on employee performance with work motivation as a moderating variable at Perum Perumnas Regional I Medan. The research approach carried out in this study used an associative approach. The population in this study were 78 permanent employees, consisting of the Accounting Section, Production Section, Land Affairs Section, Funding Section, Marketing Section, General Section and Human Resources Section. The results of this study prove that accounting information systems affect employee performance at Perum Perumnas Regional I Medan, internal control affects employee performance at Perum Perumnas Regional I Medan and key performance indicators affect employee performance at Perum Perumnas Regional I Medan. Motivation to work as a moderating variable can moderate the effect of accounting information systems on employee performance at Perum Perumnas Regional I Medan, motivation to work as a moderating variable can moderate the effect of internal control on employee performance at Perum Perumnas Regional I Medan and work motivation as a moderating variable can moderate the effect of key performance indicators on employee performance at Perum Perumnas Regional I Medan